2005
DOI: 10.1016/j.jnutbio.2004.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Reduced effect on apoptosis of 4-hydroxyhexenal and oxidized LDL enriched with n-3 fatty acids from postmenopausal women

Abstract: Background: Oxidized low-density lipoprotein (oxLDL) promotes apoptosis in atherosclerotic plaques in the vascular wall, a process mediated through its oxidized lipids. 4-Hydroxynonenal (HNE) and 4-hydroxyhexenal (HHE), derived from oxidation of n-6 and n-3 fatty acids, respectively, are among the major oxidized products in oxLDL.Hypothesis: This study hypothesized that eicosapentaenoic acid/docosahexaenoic acid (EPA/DHA)-rich versus linoleic acid-rich oxLDL obtained from postmenopausal women and HNE versus HH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…In several randomized intervention studies, but not in all [43,44], x3-PUFA from fish oil increased the susceptibility of LDL to oxidation in front of MUFA-rich [45,46] diets. One study reported differences among omega-3 fatty acids on the susceptibility of LDL to oxidation, with an increase after eicosapentanoate, but not with docosahexanoate-rich oil, when compared with an olive oil rich diet [47].…”
Section: Lipid Oxidative Damagementioning
confidence: 99%
“…In several randomized intervention studies, but not in all [43,44], x3-PUFA from fish oil increased the susceptibility of LDL to oxidation in front of MUFA-rich [45,46] diets. One study reported differences among omega-3 fatty acids on the susceptibility of LDL to oxidation, with an increase after eicosapentanoate, but not with docosahexanoate-rich oil, when compared with an olive oil rich diet [47].…”
Section: Lipid Oxidative Damagementioning
confidence: 99%
“…2004a,b; Choudhary et al. 2005; Lee and Wander 2005). HHE is a potent inducer of permeability transition in hepatic mitochondria but not mitochondria isolated from brain (Kristal et al.…”
mentioning
confidence: 99%
“…Moreover, fish ingestion has been related to a reduced risk for myocardial infarction, which may relate to beneficial effects of EPA and DHA on plaque stability (probably related to the content of inflammatory cells) and modulation of endothelial function [38]. EPA and DHA have also been shown to lower low-density lipoprotein (LDL) oxidative susceptibility in postmenopausal women, which could help to reduce the risk of CVD [39]. Primary among these is the reduction of serum triglycerides [40].…”
Section: Functional Foods With Health-related Propertiesmentioning
confidence: 99%